Evaluasi Ketepatan Antibiotik pada Pasien Sepsis - Ambar Yunita Nugraheni; Mahyastuty Shintya Putri; Adi Yusron Saputro (Universitas Muhammadiyah Surakarta, 2021)
The administration of early intravenous antibiotics was one of the fundamental procedures in sepsis. Inappropriate of antibiotics in septic patients has an impact on mortality and prolongs treatment. The purpose of this study was to evaluate the appropriateness of antibiotics therapy in hospitalized sepsis patients in Central Java based on the parameters right indication, right patient, right drug, and the right dose. This study was observational. Data collected retrospectively and analyzed descriptively. Sampling was done by purposive sampling. The inclusion criteria were inpatients diagnosed with sepsis who received antibiotics therapy with complete medical record data. The exclusion criteria were patients who died of sepsis. Antibiotics analyzed using the DIH 25th edition 2016, IONI 2014, Tata Laksana Sepsis Pada Anak IDAI 2016, Neofax 2014, Kepmenkes PNPK Tata Laksana Sepsis 2017, PPK RS, and SHC Antimicrobial Dosing 2017. Based on data from 108 patients who fulfilled the inclusion criteria obtained results right indication 100%, right patient 97.22%, right drug 90.74%, and the right dose 48.15%. The most used antibiotic was a combination of ampicillin and gentamicin (41.67%), while the single antibiotic was ceftriaxone (12.96%).